2022
DOI: 10.3389/fmicb.2022.922989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cultivated Pastures on Soil Bacterial Communities in the Karst Rocky Desertification Area

Abstract: Soil bacteria play an important role in regulating the process of vegetation restoration in karst ecosystems. However, the effects of vegetation restoration for different cultivated pastures on soil bacterial communities in the karst rocky desertification regions remain unclear. Therefore, we hypothesized that mixed pasture is the most effective for soil bacterial communities among different vegetation restorations. In this study, we systematically studied the soil properties and soil bacterial communities in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 78 publications
4
17
1
Order By: Relevance
“…In addition, revegetation by the sowing of a single species led to a reduction in the diversity of bacteria which was determined by a reduction in the plant diversity [10]. Thus, the different effects of vegetation restoration on the bacterial community's diversity may be determined by the soil nutrient status [71,72], restoration vegetation selection [62,69,72], plant diversity level [10,71,73], and restoration time [62,73]. Previous results found that the bacterial community's structure is closely related to the soil's nutrients in artificial vegetation restoration [69,70].…”
Section: Effects Of Vegetation Restoration On the Soil Bacterial Comm...mentioning
confidence: 99%
“…In addition, revegetation by the sowing of a single species led to a reduction in the diversity of bacteria which was determined by a reduction in the plant diversity [10]. Thus, the different effects of vegetation restoration on the bacterial community's diversity may be determined by the soil nutrient status [71,72], restoration vegetation selection [62,69,72], plant diversity level [10,71,73], and restoration time [62,73]. Previous results found that the bacterial community's structure is closely related to the soil's nutrients in artificial vegetation restoration [69,70].…”
Section: Effects Of Vegetation Restoration On the Soil Bacterial Comm...mentioning
confidence: 99%
“…In the natural vegetation succession, grasses are the pioneer plants for vegetation restoration and ecological improvement [ 64 ]. Meanwhile, artificial grass breeding can enrich grassland species diversity, improve grassland ecosystem stability, provide high-quality forage, reduce the risk of surface erosion, improve soil nutrient composition and provide multiple ecosystem services for humans [ 51 , 65 , 66 ]. Optimizing the spatial configuration of systems is an important means of improving the stability and resilience of grassland ecosystems [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of artificial grassland or natural recovery and secondary succession without human intervention of grassland may change the soil-plant-microorganism nutrient relationship formed by long-term evolution [23,24], thus having a profound impact on the balance of elements and substances in the ecosystem [25,26]. Up to now, research on ecological stoichiometry in karst areas has seen many achievements in vegetation succession, some vegetation (e.g., forest) or areas (e.g., grassland in northern China) [27][28][29][30][31], but research on ecological stoichiometry of the plant-soil-microorganism system in grasslands of the karst desertification control area is still very weak. At the same time, research on the C, N and P concentration of plant-soil-microorganism and ecological stoichiometry characteristics of grassland ecosystems under different restoration measures in the karst desertification control area is still insufficient.…”
Section: Introductionmentioning
confidence: 99%